2022
DOI: 10.2147/imcrj.s350858
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Dandy-Walker Syndrome

Abstract: Dandy-Walker syndrome (DWS) is a rare congenital malformation characterized by hypoplasia of the cerebellar vermis and its upward rotation and cystic enlargement of the fourth ventricle. The clinical manifestations include psychomotor retardation, ataxia and hydrocephalus. We report a case of 16-year-old female patient in Ali Abad Teaching Hospital who was suffering from unsteady gait, memory deterioration and urinary incontinence. A brain magnetic resonance imaging revealed enlarged cystic posterior fossa, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(28 reference statements)
0
2
0
2
Order By: Relevance
“…DWM is a congenital brain anomaly and over 85% of cases are discovered before the age of 1 year. Five researchers have reported that the incidence of hydrocephalus was between 86% and 94% in numerous prior studies [13] . Prenatal regular sonography throughout the antenatal period has helped some obstetricians discover this malformation [14] .…”
Section: Discussionmentioning
confidence: 99%
“…DWM is a congenital brain anomaly and over 85% of cases are discovered before the age of 1 year. Five researchers have reported that the incidence of hydrocephalus was between 86% and 94% in numerous prior studies [13] . Prenatal regular sonography throughout the antenatal period has helped some obstetricians discover this malformation [14] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that geographical location, climate, and nutritional habits all play important roles in T. gondii survival and spread (Foroutan et al, 2018). Oria et al, (2022) described a case of Dandy-Walker syndrome in a 16-year-old female patient in Kabul, which might be caused by T. gondii infection (Hamid, 2007;Ndu et al, 2015). Kozojed et al (1976) reported a high seroprevalence of toxoplasmosis (15.7 -73.7%) in domestic animals (camels, zebus, goats, sheep, buffalos and cattle).…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis depends on intra/extracranial malformations, being unfavorable for those who present these malformations, which are 50-70% of patients, with a mortality of 70% in fetuses, 14% in neonates, and 25% in infants. And favorable towards normal development within 50-65% of cases (1).…”
Section: Introductionmentioning
confidence: 94%